Analisis Hak Perempuan dalam Talaq Menurut Hukum Keluarga Islam - Mulyadi, Mulyadi (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
The aim of the research is to describe women's rights in talaq according to the view of Islamic family law. The research was conducted qualitatively using a library research approach. Data collection techniques with documentation and data processing with reduction, data presentation and conclusions. The research results show: (1) women who are divorced are women who are no longer someone else's wife and according to religious and state law still have several rights that must be granted by their ex-husband. (2) Women's rights after talaq include: First, Iddah income to meet the ex-wife's needs for 4 months and 10 days before the ex-husband reconciles. Second, madliyah income is given by the husband to his wife and children because of negligence during marriage. The three mut'ah livelihoods are given by the husband to please his ex-wife in living life after divorce. The four dowry debts are given by the husband, either in part or in full, to the wife.